The relationship between erythrocyte indexes (MCV, MCH, MCHC) as indicators of parasitic anemia in carp (Cyprinus carpio) supplemented with bromelain enzyme - Adimas Bagus Fahturohman; Zakyatul Muna; Farid Mukhtar Riyadi; Wijayanti Ristyaningrum; I Kadek Sumiana (Jurnal Perikanan Terpadu, 2026)
Goldfish cultivation currently faces several major problems, such as the high prevalence of parasitic infections, particularly those caused by Argulus japonicus. This study aims to identify and analyze the relationship between MCV, MCH, and MCHC values as indicators of parasitic anemia in goldfish (Cyprinus carpio) infested with Argulus japonicus and the effect of bromelain enzyme supplementation in commercial feed. The research stages include aquarium and maintenance media preparation, bromelain enzyme production from pineapple core, treatment feed production, and Argulus japonicus culture. The experiment employed a factorial-based Completely Randomized Design (CRD) comprising eight treatment combinations, and data analysis utilized the Pearson correlation test in conjunction with multiple linear regression. The results showed a strong positive relationship between MCV and MCH, reflecting normal erythropoiesis, in which erythrocyte enlargement is followed by an increase in hemoglobin per cell. In practice, these findings can be used to detect anemia early, potentially reducing aquaculture productivity. The application of the results of this research can potentially increase fish resistance to disease and support production efficiency in intensive fish farming